The problem of consistency of Ukrainian private law with the provisions of Directive 2019/771 on consumer rights in case of non-conformity of the goods transferred under the sales contract - Tomala, Margaryta; Zoll, Frederick (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The publication is devoted to the study of the problems of adaptation of Directive 2019/771 of the European Parliament and the Council on certain aspects of contracts for the sale of goods dated 05/20/2019 under Ukrainian legislation. The publication carried out a comparative analysis of the provisions of Directive 2019/771 on the legal consequences of the non-conformity of goods transferred under the sales contract with the terms of the contract and the provisions of the national legislation on the protection of consumer rights. Taking into account the European integration vector of the development of national legislation and Ukraine᾽s obtaining the status of a candidate country for EU membership, the question of adapting the relevant European legal acts to the national legal order is extremely relevant. The purpose of the article is to clarify the key problems of Ukrainian private law in the field of contractual relations of purchase and sale of consumer goods and to formulate possible models of adaptation of Directive 2019/771 – «copy & paste» and models of Europeanization.Despite the existence in the national legislation of Ukraine of a disconnection of the normative regulation of contractual relations of purchase and sale and the accumulation of terminological concepts in these acts, the approach to the legal consequences of the transfer of goods of inadequate quality is quite rational. To strengthen the provisions of the private law of Ukraine, authors consider it necessary to unify the national civil legislation by enshrining all the main regulatory norms in the fundamental legal act – the Civil Code of Ukraine and harmonizing the relevant laws with its provisions. The authors proved that the Europeanization model of the adaptation of Directive 2019/771 is the most effective since its application will not only allow adapting national legislation to European standards but will also positively affect the systematization of existing legislative provisions.